From Resistance to Digital Technologies in the Context of the Reaction to Distance Learning in the School Context during COVID-19 - Giusi Antonia Toto; Pierpaolo Limone (MDPI AG, 2021)
In the relationship between teachers and distance learning in the context of COIVD-19, a series of unprecedented dynamics have emerged relating to a process of open-air experimentation that is going on in the world of school. The main constructs investigated in this paper concern the professional perceptions of teachers in terms of their skills and resistances towards digital technologies. To investigate this topic, a questionnaire on distance learning was administered to a sample of 658 teachers. From a methodological point of view, factor and reliability analyses and correlation and regression analyses were conducted. From the analysis of the results, it emerged that the questionnaire measures the resistance of teachers to distance learning and focuses on three main dimensions (two positive and one negative) that link teachers' perceptions to the resistance to distance learning. In conclusion, the theme of the acceptance of technologies in the practice of teachers is still a subject full of meaning for professional perception and vision. A second issue concerns precisely the relationship between digital technologies and users, which must no longer focus only on the relationship with students but also on the perspective of the other training actors, including teachers.